NAB-paclitaxel and gemcitabine in metastatic pancreatic ductal adenocarcinoma (PDAC): from clinical trials to clinical practice. Issue 1 (December 2016) - De Vita, Ferdinando; Ventriglia, Jole; Febbraro, Antonio; Laterza, Maria; Fabozzi, Alessio; Savastano, Beatrice; Petrillo, Angelica; Diana, Anna; Giordano, Guido; Troiani, Teresa; Conzo, Giovanni; Galizia, Gennaro; et al.
Abstract Background Pancreatic adenocarcinoma is an aggressive disease with poor prognosis. In a randomized phase III trial, combination of Nab-paclitaxel (Nab-P) plus gemcitabine showed superior activity and efficacy in first-line treatment compared with gemcitabine alone. Methods Nab-P is not dispensed in Italy; however, we obtained this drug from our Ethics Committee for compassionate use. The aim of this study was to evaluate the efficacy and safety profile of this Nab-P and gemcitabine combination in a cohort of patients treated outside clinical trials. From January 2012 to May 2014, we included 41 patients with advanced pancreatic adenocarcinoma receiving combination of 125 mg/m2 Nab-P and 1 g/m2 gemcitabine on days 1, 8 and 15 of a 28-day cycle, as first-line treatment. Median age of patients was 67 (range 41–77) years, and 11 patients were aged ≥70 years. Results Eastern Co-operative Oncology Group performance status was 0 or 1 in 32 patients (78 %) and 2 in nine patients (22 %). Primary tumor was located in the pancreatic head or body/tail in 24 (58.5 %) and 17 (41.5 %) patients, respectively, and nine patients had received biliary stent implantation before starting chemotherapy. Median carbohydrate antigen 19–9 level was 469 U/l (range 17.4–61546 U/l) and 29 patients (70.7 %) had referred pain at the time of diagnosis. Patients received a median six cycles (range 1–14) of treatment. Overall response rate was 36.6 %; median progression-free survival was 6.7 months [(95 % confidence interval (CI) 5.966–8.034), and median overall survival was 10 months (95 % CI 7.864–12.136). Treatment was well tolerated. No grade 4 toxicity was reported. Grade 3 toxicity included neutropenia in 10 patients (24.3 %), thrombocytopenia in five (12 %), anemia in three (7.3 %), diarrhea in four (9.7 %), nausea and vomiting in two (4.9 %), and fatigue in six (14.6 %). Finally, pain control was achieved in 24 of 29 patients (82.3 %) with a performance status improvement of 10 % according to the Karnofsky scale. Conclusions Our results confirm that combination of gemcitabine plus Nab-P is effective both in terms of overall response rate, progression-free survival and overall survival, with a good safety profile.